HIV-Associated Neurotoxicity: The Interplay of Host and Viral Proteins. (25th August 2021) - Jadhav, Sushama; Nema, Vijay
Abstract : HIV-1 can incite activation of chemokine receptors, inflammatory mediators, and glutamate receptor-mediated excitotoxicity. The mechanisms associated with such immune activation can disrupt neuronal and glial functions. HIV-associated neurocognitive disorder (HAND) is being observed since the beginning of the AIDS epidemic due to a change in the functional integrity of cells from the central nervous system (CNS). Even with the presence of antiretroviral therapy, there is a decline in the functioning of the brain especially movement skills, noticeable swings in mood, and routine performance activities. Under the umbrella of HAND, various symptomatic and asymptomatic conditions are categorized and are on a rise despite the use of newer antiretroviral agents. Due to the use of long-lasting antiretroviral agents, this deadly disease is becoming a manageable chronic condition with the occurrence of asymptomatic neurocognitive impairment (ANI), symptomatic mild neurocognitive disorder, or HIV-associated dementia. In-depth research in the pathogenesis of HIV has focused on various mechanisms involved in neuronal dysfunction and associated toxicities ultimately showcasing the involvement of various pathways. Increasing evidence-based studies have emphasized a need to focus and explore the specific pathways in inflammation-associated neurodegenerative disorders. In the current review, we have highlighted the association of various HIV proteins and neuronal cells with their involvement in various pathways responsible for the development of neurotoxicity.